Effects of NaCl and NaNO3 on the capillary suction, drying kinetics and vapour permeability of three building stones. - Brito, V. (2012)
Salt decay is closely related to drying of porous materials, not only as a consequence but also because the salts are an influencing factor in drying processes. This influence, however, is not yet totally clear, as are not in general the effects of soluble salts on liquid and vapour transport through complex pore networks such as those of porous building materials. Here, we analyse the role of two soluble salts, NaCl and NaNO3, on the capillary suction and drying kinetics of three natural stones. The physical morphology of the efflorescence layer occurring in each case and the effect of such layer on vapour transport are also analysed.